Flame-retardant ABS (Acrylonitrile Butadiene Styrene) composition and preparation method and application thereof
By leveraging the synergistic effect of aluminum phosphonate and oxides with brominated flame retardants, the problem of ABS materials failing to achieve V-0 flame retardancy rating and insufficient light transmittance at low addition levels has been solved, achieving both high-efficiency flame retardancy and high light transmittance.
Patent Information
- Application Number
- CN202511344038.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-19
- Publication Date
- 2025-11-21
AI Technical Summary
Existing commercial flame-retardant ABS materials struggle to achieve a V-0 flame retardant rating while maintaining high light transmittance at low additive levels. The addition of bromine-based flame retardants and antimony trioxide leads to a decrease in light transmittance.
A synergistic flame retardant system is adopted, consisting of aluminum phosphonate flame retardant, oxides, and brominated flame retardants. At high temperatures, aluminum phosphonate forms liquid phosphorus, which acts as a barrier in the condensed phase. The oxides pyrolyze to produce bromides, which synergistically retard flames in both the condensed and gas phases. The antimony content is reduced to improve light transmittance.
Achieving a V-0 flame retardant rating with low addition levels while maintaining a light transmittance of over 30% reduces the amount of flame retardant used and lowers costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of high molecular flame-retardant materials, and particularly relates to a flame-retardant ABS composition and a preparation method and application thereof. BACKGROUND
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) refers to a graft copolymer of polybutadiene rubber and monomer polystyrene, which has gloss and processing fluidity of polystyrene (PS), impact resistance of polybutadiene (PB) rubber, rigidity and drug resistance of polyacrylonitrile (PAN), and excellent processing performance, electroplating performance and high gloss appearance, and is one of the most used thermoplastic engineering plastics, and has very wide application in the manufacturing industries of industrial instruments, automobiles, household appliances and toys.
[0003] However, ABS is flammable, has a low oxygen index (only 19%), has a very fast horizontal burning speed, and releases a large amount of black smoke and toxic gas during burning, which greatly limits its application in the fields such as electronic appliances and building materials which have strict requirements on flame retardation, so flame retardation of ABS is particularly important.
[0004] The existing commercial flame-retardant ABS mainly adopts a bromine-based flame-retardant system, and takes decabromodiphenyl ethane and brominated epoxy resin as main flame retardants and antimony trioxide as a synergist. Although the system can obtain a high flame-retardant grade, the addition amount of the bromine-based flame retardant and antimony trioxide is usually high, most of the bromine-based flame retardants (such as decabromodiphenyl ethane and tetrabromobisphenol A) are aromatic or aliphatic bromine-containing compounds, contain a large number of benzene rings or high-density bromine atoms in the molecules, have high refractive index, are easy to scatter light, and reduce the light transmittance of the material, and the antimony trioxide is a white inorganic powder, which also causes the light transmittance to decrease.
[0005] Therefore, how to achieve V-0 flame-retardant grade and simultaneously maintain high light transmittance at a low flame-retardant addition amount is a technical problem to be solved in the field at present. SUMMARY
[0006] In view of the deficiencies in the prior art, the purpose of the present application is to provide a flame-retardant ABS composition and a preparation method and application thereof. The flame-retardant ABS composition can achieve excellent flame-retardant effect and has high light transmittance at a low flame-retardant addition amount.
[0007] To achieve the purpose, the present application adopts the following technical solutions:
[0008] In a first aspect, the present application provides a flame-retardant ABS composition, which comprises the following components in parts by weight:
[0009] In a first aspect, the present application provides a flame-retardant ABS composition, which comprises the following components in parts by weight:
[0010] In the present application, 66-80 parts of ABS resin, for example, can be 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts or a range between any of the above values, the mass percentage content of ABS resin in the flame-retardant ABS composition provided by the present application accounts for 56.9-95.8%. In the present application, the melt flow rate of the ABS resin under the condition of 220℃ and 10kg is 25-40g / 10min, for example, can be 25g / 10min, 26g / 10min, 28g / 10min, 30g / 10min, 32g / 10min, 34g / 10min, 36g / 10min, 38g / 10min or 40g / 10min or a range between any of the above values.
[0011] In the present application, 13-21 parts of bromine-based flame retardant, for example, can be 13 parts, 14 parts, 14.2 parts, 14.6 parts, 14.8 parts, 15 parts, 15.2 parts, 15.4 parts, 15.6 parts, 15.8 parts, 16 parts, 16.2 parts, 16.4 parts, 16.6 parts, 16.8 parts, 17 parts, 17.2 parts, 17.4 parts, 17.6 parts, 17.8 parts, 18 parts, 18.2 parts, 18.4 parts, 18.6 parts, 18.8 parts, 19 parts, 19.2 parts, 19.4 parts, 19.6 parts, 19.8 parts, 20 parts, 21 parts or a range between any of the above values, the mass percentage content of bromine-based flame retardant in the flame-retardant ABS composition provided by the present application accounts for 11.2-25.2%.
[0012] In the present application, 4-11 parts of aluminum phosphonate flame retardant, for example, can be 4 parts, 4.5 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts, 9 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts, 10 parts, 10.5 parts, 11 parts or a range between any of the above values, the mass percentage content of aluminum phosphonate flame retardant in the flame-retardant ABS composition provided by the present application accounts for 4-11%.
[0013] In the present application, 0.5-4 parts of oxide, for example, can be 0.5 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts or a range between any of the above values, the mass percentage content of oxide in the flame-retardant ABS composition provided by the present application accounts for 0.5-4%.
[0014] In the present application, the synergistic flame retardation is achieved by using aluminum phosphinate flame retardant, oxide and bromine flame retardant in the flame-retardant ABS composition. The aluminum phosphinate flame retardant is more likely to melt and form liquid phosphorus at high temperature, which plays a barrier role in the condensed phase. The oxide and bromine flame retardant produce bromide (halogen salt) through pyrolysis, which plays a barrier role in the condensed phase, further compacts and enhances the heat shield barrier. At the same time, the bromine flame retardant plays a gas phase flame retardation role in the pyrolysis process, and the gas phase and condensed phase synergistically retard flame, improve the flame retardation efficiency, and can achieve V-0 flame retardation level while considering excellent optical performance and improving the light transmittance of the material. It should be noted that the flame-retardant ABS composition described in the present application basically does not contain antimony. "Basically does not contain antimony" means that the concentration of antimony (for example, diantimony trioxide) in the composition is much lower than the acceptable amount of plastic products used in combination with halogenated additives in styrene formulations, for example, the mass percentage is not more than 0.3%, more preferably at most 0.2%, for example 0-0.1% (based on the total mass of the flame-retardant ABS composition). Most preferably, the composition of the present application does not contain antimony at all.
[0015] Preferably, the structure of the aluminum phosphinate flame retardant is as follows:
[0016]
[0017] wherein R1, R2, R3, R4, R5, R6 are each independently -OH, -C2H5, -C4H9, -C6H 13 or -C8H 15 .
[0018] In the present application, the aluminum phosphinate flame retardant can be obtained from commercially available raw materials or self-made by existing process. The self-made method includes but is not limited to the following methods:
[0019] First, mix alkyl hypophosphite and sodium hydroxide solution, control the pH value of the reaction end point to be 7-9, to obtain sodium hypophosphite solution; then mix sodium hypophosphite solution and aluminum salt solution, obtain aluminum hypophosphite through precipitation reaction, then separate the solid product by filtration, and then dry to obtain aluminum phosphinate flame retardant. The aluminum salt includes but is not limited to at least one of AlCl3, Al2(SO4)3 or Al(NO3)3. Preferably, the mass percentage of rubber in the ABS resin is 18-23%, for example, it can be 18%, 18.2%, 18.4%, 18.6%, 18.8%, 19%, 19.2%, 19.4%, 19.6%, 19.8%, 20%, 20.2%, 20.4%, 20.6%, 20.8%, 21%, 21.2%, 21.4%, 21.6%, 21.8%, 22%, 22.2%, 22.4%, 22.6%, 22.8%, 23% or a range between any of the above values.
[0020] In the present application, the ABS resin is obtained by bulk method or emulsion method, preferably emulsion method.
[0021] Preferably, the bromine-based flame retardant comprises at least one of decabromodiphenyl ethane, brominated triazine, brominated epoxy resin or brominated polystyrene.
[0022] Preferably, the oxide comprises at least one of magnesium oxide, calcium oxide, arsenic oxide, bismuth oxide or organic phosphorus oxide.
[0023] Preferably, the organic phosphorus oxide comprises bis(p-tolyl)phosphine oxide and / or bis(4-methoxyphenyl)phosphine oxide.
[0024] Preferably, the oxide comprises bismuth oxide or a combination of bismuth oxide and arsenic oxide.
[0025] In the present application, by preferably controlling the oxide to be a combination of arsenic oxide and bismuth oxide, in the thermal degradation stage, the arsenic oxide can generate high-density arsenic salt products with halides, and the bismuth oxide can also form high-density bismuth salt products with halides in the pyrolysis process, and the two high-density salts can enhance the barrier and covering effects, thereby synergistically retarding the flame, achieving excellent flame-retardant effect.
[0026] Preferably, the mass ratio of arsenic oxide to bismuth oxide in the oxide is 1:(0.5-10), for example, it can be 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range between any of the above values.
[0027] In the present application, by preferably controlling the mass ratio of arsenic oxide to bismuth oxide in the oxide, the flame-retardant effect can be further improved.
[0028] Preferably, the D50 particle size of the oxide is 10-50 μm, for example, it can be 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm or a range between any of the above values.
[0029] In the present application, by preferably controlling the D50 particle size of the oxide, better dispersion in the polymer material can be achieved, the compatibility can be improved, the excellent mechanical properties can be maintained, and higher flame-retardant efficiency can be achieved.
[0030] In the present application, the testing method of the D50 particle size of the oxide is as follows: the oxide is dispersed in anhydrous ethanol solvent by ultrasonic dispersion, a uniformly dispersed solution with a mass concentration of 8-12% is configured, the sample is uniformly dispersed to avoid agglomeration, and a laser particle size analyzer is used for testing.
[0031] Preferably, the thermal decomposition temperature of the oxide is >600℃, for example, can be 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, or a range between any of the above values, preferably >800℃, further preferably >900℃.
[0032] In the present application, by preferably controlling the thermal decomposition temperature of the oxide, degradation at high temperature can be achieved, and better flame retardant effect can be achieved. If the decomposition temperature is low, the flame retardant effect is poor.
[0033] In the present application, the testing method of the thermal decomposition temperature of the oxide is as follows: a thermogravimetric method is used for testing, the heating rate is 15-25℃ / min, the atmosphere is nitrogen, the thermal weight loss step of the TG curve is analyzed, the thermal decomposition temperature of the oxide is determined, and the starting point temperature of the weight loss step can be considered as the thermal decomposition temperature of the oxide.
[0034] Preferably, the specific surface area of the oxide is 10-50m 2 / g, for example, can be 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 24m 2 / g, 26m 2 / g, 28m 2 / g, 30m 2 / g, 32m 2 / g, 34m 2 / g, 36m 2 / g, 38m 2 / g, 40m 2 / g, 42m 2 / g, 44m 2 / g, 46m 2 / g, 48m 2 / g, 50m 2 / g or a range between any of the above values.
[0035] In the present application, by preferably controlling the specific surface area of the oxide, the mechanical strength of the composite material can be improved through interfacial interaction.
[0036] In the present application, the surface area of the oxide is measured by measuring the multilayer adsorption amount of nitrogen gas at liquid nitrogen temperature (-196℃), calculating the monolayer adsorption amount, and then obtaining the specific surface area.
[0037] Preferably, the mass ratio of bromine-based flame retardant, aluminum phosphonate flame retardant and oxide in the flame-retardant ABS composition is (14-20):(5-10):(1-4), for example, it can be 14:5:1, 15:6:1, 18:7:2, 19:8:3, 20:9:4, 20:10:1 or a range between any of the above values.
[0038] In the present application, by preferably controlling the mass ratio of bromine-based flame retardant, aluminum phosphonate flame retardant and oxide, the synergistic flame-retardant effect can be further played, the addition amount of flame retardant is reduced while achieving V-0 flame-retardant grade, the light transmittance is improved, and the cost is reduced.
[0039] Without affecting the effect of the flame-retardant ABS composition described in the present application, other auxiliary agents can also be added as needed, including but not limited to one or more of antioxidants, lubricants or anti-dripping agents.
[0040] Specifically, the flame-retardant ABS composition contains 0.1-0.5 parts of antioxidant, for example, it can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or a range between any of the above values.
[0041] The antioxidant can be selected according to the prior art, including but not limited to one or more of phenolic antioxidant, phosphite antioxidant, divalent sulfur antioxidant or hindered amine antioxidant.
[0042] The phenolic antioxidant includes one or more of 2,6-di-tert-butyl-4-methylphenol (antioxidant 264), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexyleneglycol (antioxidant 1098), n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), styrenated phenol (antioxidant SP), 2,2'-methylenebis(4-methyl-6-tert-butylphenol) (antioxidant 2246), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane (antioxidant CA), 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (antioxidant 330), or 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) (antioxidant 3114). The phosphite antioxidant includes one or more of tris(nonylphenyl)phosphite (antioxidant TNP), reaction product of N-phenylphenylenediamine and 2,4,4-trimethylpentene (antioxidant ODP), tris[2,4 di-tert-butylphenyl]phosphite (antioxidant 168), bis(4-octylphenyl)diphosphate (antioxidant 1093), or diethyl 3,5-di-tert-butyl-4-hydroxybenzoate (antioxidant 1222). The divalent sulfur antioxidant includes dilaurylthiodipropionate (DLTP) and / or distearylthiodipropionate (DSTP). The hindered amine antioxidant includes one or more of LS-744, bis-2,2,6,6-tetramethylpiperidinyl sebacate (e.g., LS-770), tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite (GW-540), or Flamstab NOR 116.
[0043] In particular, the flame retardant ABS composition includes 0.1 to 2 parts of a lubricant, such as 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1.0 part, 1.2 part, 1.4 part, 1.6 part, 1.8 part, 2 part, or a range between any of the foregoing values.
[0044] The lubricant can be selected from the prior art, including but not limited to one or more of stearic acid amide, pentaerythritol stearate, or stearate.
[0045] In particular, the flame retardant ABS composition includes 0.1 to 0.5 parts of an anti-dripping agent, such as 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, or a range between any of the foregoing values.
[0046] The anti-dripping agent can be selected according to the prior art, including but not limited to polytetrafluoroethylene, which can be SN80-SA7, POLY TS 30A, PTFE-200D, etc. It should be noted that although the polytetrafluoroethylene anti-dripping agent can further improve the flame retardant effect, it has biological toxicity, which is increasingly unsatisfactory to environmental protection requirements, and affects the light transmittance of the product, therefore, fluorine-free flame retardant is the development trend of flame retardant materials at present.
[0047] In a second aspect, the present application provides a preparation method of the flame-retardant ABS composition according to the first aspect of the present application, which comprises the following steps:
[0048] After melt blending of the components, extrusion granulation, drying, the flame-retardant ABS composition is obtained.
[0049] Preferably, the preparation method of the flame-retardant ABS composition specifically comprises the following steps:
[0050] (1) uniformly mixing the components to obtain a mixed raw material;
[0051] (2) melting, mixing and extruding the mixed raw material obtained in step (1), then granulating and drying to obtain the flame-retardant ABS composition.
[0052] Preferably, the mixing in step (1) is carried out in a high-speed mixer.
[0053] Preferably, the rotation speed of the mixing in step (1) is 800-1000 r / min, for example, it can be 800 r / min, 810 r / min, 820 r / min, 830 r / min, 840 r / min, 850 r / min, 860 r / min, 870 r / min, 880 r / min, 890 r / min, 900 r / min, 910 r / min, 920 r / min, 930 r / min, 940 r / min, 950 r / min, 960 r / min, 970 r / min, 980 r / min, 990 r / min, 1000 r / min or a range between any of the above values.
[0054] Preferably, the mixing time in step (1) is 2-5 min, for example, it can be 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min or a range between any of the above values.
[0055] Preferably, the melting in step (2) is carried out in a twin-screw extruder.
[0056] Preferably, the temperature of the melting is 190-215℃, for example, it can be 190℃, 192℃, 194℃, 196℃, 198℃, 200℃, 202℃, 204℃, 206℃, 208℃, 210℃, 212℃, 214℃, 215℃ or a range between any of the above values.
[0057] Preferably, the screw rotation speed of the twin-screw extruder is 300-500 r / min, for example, it can be 300 r / min, 320 r / min, 340 r / min, 360 r / min, 380 r / min, 400 r / min, 420 r / min, 440 r / min, 460 r / min, 480 r / min, 500 r / min or a range between any of the above values.
[0058] In a third aspect, the present application provides a flame-retardant product, which is formed by the flame-retardant ABS composition according to the first aspect of the present application.
[0059] The present application provides the use of the above-mentioned flame-retardant ABS composition in the preparation of toys, household products, office supplies, electronic components, household appliances, gardening equipment, medical technology equipment, motor vehicle parts or vehicle body parts. In particular, the above-mentioned flame-retardant ABS composition is used in the field of preparing products with excellent flame-retardant properties and light transmission properties; for example, in the field of products such as video multimedia DVD, audio, television, etc.
[0060] The numerical ranges of the present application include not only the above-mentioned point values, but also any point values between the above-mentioned numerical ranges which are not listed. Due to the limited space and for the sake of simplicity, the present application does not list all the specific point values included in the above-mentioned ranges.
[0061] Compared with the prior art, the present application has the following advantages:
[0062] The flame-retardant ABS composition provided by the present application uses aluminum phosphonate flame retardant, oxide and bromine-based flame retardant for synergistic flame retardation. At high temperatures, the aluminum phosphonate flame retardant is more likely to melt to form liquid phosphorus, which plays a barrier role in the condensed phase. The oxide and the bromine-based flame retardant produce bromide (halide salt) through pyrolysis, which plays a condensed phase barrier role, further densifies and enhances the heat shielding barrier. At the same time, the bromine-based flame retardant plays a gas phase flame retardation role in the pyrolysis process, and the gas phase and the condensed phase synergistically flame retard, improving the flame retardation efficiency. The flame-retardant ABS composition can achieve V-0 flame-retardant grade while taking into account excellent optical performance, improving the light transmittance of the material, and the light transmittance is more than 30%. DETAILED DESCRIPTION
[0063] The technical solutions of the present application are further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present application and should not be regarded as specific limitations of the present application.
[0064] In the present application, the materials used in the examples and comparative examples are all commercially available or prepared by conventional methods. Unless otherwise specified, the materials used in the present application are as follows:
[0065] ABS resin:
[0066] ABS AG15AA-H, Taiwan Chemical Fibre Co., Ltd., rubber mass percentage of 18%.
[0067] Bromine-based flame retardant:
[0068] Bromine-based flame retardant 1, bromine-containing triazine, FR-245, Isram Chemicals Ltd.
[0069] Bromine-based flame retardant 2, brominated epoxy, F-3014, Isram Chemicals Ltd.
[0070] Aluminum phosphinate flame retardant:
[0071] Aluminum phosphinate flame retardant 1, with the following structure:
[0072]
[0073] wherein R1, R2, R3, R4, R5, and R6 are all -C4H9, and the preparation method is as follows:
[0074] To diisobutyl hypophosphite with a water content of 75%, a 50% mass concentration sodium hydroxide solution was added dropwise and neutralized, and the pH value of the reaction was controlled to 7.2. Then water was added for dilution to obtain a 8% mass concentration sodium diisobutyl hypophosphite solution. Then a 30% mass concentration aluminum chloride solution was added to the sodium diisobutyl hypophosphite solution, and aluminum diisobutyl hypophosphite was precipitated. After vacuum-assisted filtration, the white powder product was dried at 120°C to obtain aluminum diisobutyl hypophosphite with a yield of 99%.
[0075] Aluminum phosphinate flame retardant 2, with the following structure:
[0076]
[0077] wherein R1, R2, R3, R4, R5, and R6 are all -C2H5, and the preparation method is as follows:
[0078] A diethyl hypophosphite solution with a mass concentration of 8% was obtained by adding a 50% mass concentration sodium hydroxide solution to diethyl hypophosphite with a water content of 75% to perform a neutralization reaction, controlling the pH end point to be 7.2, and then diluting with water. Then, aluminum diethyl hypophosphite was precipitated by adding a 30% mass concentration aluminum chloride solution to the diethyl hypophosphite solution, vacuum-assisted filtration was performed, and then drying was performed at 120°C to obtain the product, white powder, aluminum diethyl hypophosphite, with a yield of 99%.
[0079] Oxide
[0080] Oxide 1, bismuth oxide, Shanghai Aladdin Reagent Co., Ltd., thermal decomposition temperature > 900°C;
[0081] Oxide 2, arsenic oxide, Shanghai Aladdin Reagent Co., Ltd., thermal decomposition temperature > 900°C;
[0082] Oxide 3, magnesium oxide, Shanghai Aladdin Reagent Co., Ltd., thermal decomposition temperature > 800°C;
[0083] Oxide 4, bis(4-methoxyphenyl)phosphorus oxide, Shanghai Aladdin Reagent Co., Ltd., thermal decomposition temperature > 600°C.
[0084] Examples 1-12 and Comparative Examples 1-7 each provide a flame-retardant ABS composition, the composition of which is shown in Tables 1-3 in terms of parts by weight.
[0085] In Tables 1-3, " / " indicates that the component is not present in the formulation.
[0086] In the present application, unless otherwise specified, the method for preparing the flame-retardant ABS composition comprises:
[0087] (1) uniformly mixing the components in a high-speed mixer at a speed of 900-910 r / min for 4 min to obtain a mixed raw material;
[0088] (2) feeding the mixed raw material obtained in step (1) into a twin-screw extruder to melt, mix and extrude, the melting temperature being 200-205°C, the screw speed of the twin-screw extruder being 400-410 r / min, and the length-diameter ratio of the twin-screw extruder being 40:1, and then pelletizing and drying to obtain the flame-retardant ABS composition.
[0089] Table 1
[0090]
[0091] Table 2
[0092]
[0093]
[0094] Table 3
[0095]
[0096] Performance test:
[0097] (1) Flame retardant grade: according to UL 94-2021 test, the detection item is vertical burning, and the thickness of the burning sample is 2.0mm.
[0098] (2) Light transmittance: the test method is to place a standard white plate in the sample position, record the intensity of the incident light, and obtain a reference value of 100% transmittance. Remove the standard white plate, place a 2mm thick square sample in the light path, ensure that the sample is flat and completely covers the test window, record the light intensity after the sample, and record the light transmittance result when the light is incident at an angle of 60°.
[0099] The specific test results are shown in Table 4.
[0100] Table 4
[0101] Flame retardant class Transmittance / % Example 1 V-0 38 Example 2 V-0 36 Example 3 V-0 34 Example 4 V-0 32 Example 5 V-0 31 Example 6 V-0 33 Example 7 V-0 31 Example 8 V-0 32 Example 9 V-0 30 Example 10 V-0 35 Example 11 V-0 34 Example 12 V-0 34 Comparative Example 1 V-1 35 Comparative Example 2 V-2 not achieved 40 Comparative Example 3 V-2 not achieved 41 Comparative Example 4 V-2 not achieved 36 Comparative Example 5 V-0 15 Comparative Example 6 V-1 32 Comparative Example 7 V-0 13
[0102] As can be seen from Table 4, the flame-retardant ABS composition provided by the present application, by using aluminum phosphonate flame retardant, oxide and bromine-based flame retardant for synergistic flame retardation, the aluminum phosphonate flame retardant is more likely to melt to form a liquid phosphorus at high temperature, which plays a barrier role in the condensed phase, and the oxide and bromine-based flame retardant produce bromide (halide salt) through pyrolysis, which plays a condensed phase barrier role, further densifies and enhances the heat shield barrier; at the same time, the bromine-based flame retardant plays a gas phase flame retardation role in the pyrolysis process, the gas phase and condensed phase synergistically flame retard, improve the flame retardation efficiency, can achieve V-0 flame retardation grade while taking into account excellent optical performance, improve the light transmittance of the material, the light transmittance is more than 30%.
[0103] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present application, and it should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A flame-retardant ABS composition, characterized in that, The flame-retardant ABS composition comprises the following components by weight fraction:
2. The flame retardant ABS composition according to claim 1, characterized in that, The structure of the aluminum phosphinate flame retardant is as follows: wherein R1, R2, R3, R4, R5, R6 are each independently -OH, -C2H5, -C4H9, -C6H 13 or -C8H 15 any of the above.
3. The flame retardant ABS composition according to claim 1, characterized in that, The mass percentage of rubber in the ABS resin is 18-23%.
4. The flame retardant ABS composition according to claim 1, characterized in that, The bromine-based flame retardant comprises at least one of decabromobiphenyl ethane, brominated triazine, brominated epoxy resin or brominated polystyrene.
5. The flame retardant ABS composition according to claim 1, characterized in that, The oxide comprises at least one of magnesium oxide, calcium oxide, arsenic oxide, bismuth oxide or organic phosphorus oxide; The organic phosphorus oxide comprises bis(p-tolyl)phosphine oxide and / or bis(4-methoxyphenyl)phosphine oxide.
6. The flame retardant ABS composition according to claim 5, characterized in that, The oxide comprises bismuth oxide or a combination of bismuth oxide and arsenic oxide. Preferably, the mass ratio of arsenic oxide to bismuth oxide in the oxide is 1:(0.5-10).
7. The flame retardant ABS composition according to claim 1, characterized in that, The D50 particle size of the oxide is 10-50 μm. Preferably, the specific surface area of the oxide is between 10 and 50 m 2 / g.
8. The flame retardant ABS composition according to claim 1, characterized in that, The mass ratio of the bromine-based flame retardant, the aluminum phosphinate flame retardant and the oxide in the flame-retardant ABS composition is (14-20):(5-10):(1-4).
9. A process for the preparation of a flame-retardant ABS composition according to any one of claims 1 to 8, characterized in that, The preparation method comprises the following steps: After melt blending of the components, extrusion granulation and drying, the flame-retardant ABS composition is obtained.
10. A flame-retardant article, characterized by, The flame-retardant product is formed from the flame-retardant ABS composition according to any one of claims 1-8.
Citation Information
Patent Citations
Flame-retarded styrene-containing compositions
CN110520467A
ABS composite material and preparation method thereof
CN112143162A
Flame-retardant ABS (Acrylonitrile Butadiene Styrene) composition and preparation method and application thereof
CN119842179A
Polyamide resin composition
JP2014122329A
Antimony-free flame-retardant polypropylene composition and preparation method therefor
WO2021164353A1
Cited By
Thermoplastic resin composition as well as preparation method and product thereof
CN122127730A